2009
DOI: 10.1002/syn.20689
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonist histamine H3 receptor PET tracers labelled with carbon‐11 or fluorine‐18

Abstract: Two histamine H3 receptor (H3R) inverse agonist PET tracers have been synthesized and characterized in preclinical studies. Each tracer has high affinity for the histamine H3 receptor, has suitable lipophilicity, and neither is a substrate for the P-glycoprotein efflux pump. A common phenolic precursor was used to synthesize each tracer with high specific activity and radiochemical purity by an alkylation reaction using either [(11)C]MeI or [(18)F]FCD(2)Br. Autoradiographic studies in rhesus monkey and human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Agonist-induced signaling, such as that which occurs in the presence of elevated histamine levels, This study demonstrates the utility of PET scanning to characterize the pharmacodynamic occupancy profile of different potential compounds for the H3 target to inform the rational selection of optimal dosing for future clinical evaluations. In vivo H3 receptor brain distribution using 11 C-MK-8278 was in qualitative agreement with autoradiography data in humans (15) and that reported for 11 C-GSK189254 (16), indicating suitability of the 11 C-MK-8278 for demonstrating H3 receptor sites in the brain in vivo. The development of radioligands for PET imaging of receptors in the CNS is a demanding task, and although binding has been demonstrated for many radioligands for the H3, only a few are suitable for applied quantitative studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Agonist-induced signaling, such as that which occurs in the presence of elevated histamine levels, This study demonstrates the utility of PET scanning to characterize the pharmacodynamic occupancy profile of different potential compounds for the H3 target to inform the rational selection of optimal dosing for future clinical evaluations. In vivo H3 receptor brain distribution using 11 C-MK-8278 was in qualitative agreement with autoradiography data in humans (15) and that reported for 11 C-GSK189254 (16), indicating suitability of the 11 C-MK-8278 for demonstrating H3 receptor sites in the brain in vivo. The development of radioligands for PET imaging of receptors in the CNS is a demanding task, and although binding has been demonstrated for many radioligands for the H3, only a few are suitable for applied quantitative studies.…”
Section: Discussionsupporting
confidence: 87%
“…2), the highest binding densities were in the ventral pallidal and basal nuclei, nucleus accumbens, substantia nigra, and globus pallidus. Moderate binding was found in other parts of the brain, and the thalamic nuclei (ventral lateral) and brain stem exhibited minimal binding (15). MK-8278 is a poor substrate for human P-glycoprotein, with a transport ratio of 2.3, and shows low plasma protein binding (82% in humans).…”
Section: C-mk-8278 Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, a lack of increase in brain uptake obtained with a P-gp modulator does not necessarily mean that there is no P-gp-mediated transport. Some newly developed central nervous system radiotracers designed for histamine H 3 receptor mapping were recently tested in an in vitro model of human P-gp to ensure that they did not interact with P-gp at a preclinical stage (37). However, there is a real need to determine how the compounds used for PET are transported by human P-gp and BCRP (6).…”
Section: Discussionmentioning
confidence: 99%
“…There is active interest in developing drugs targeted to the H 3 receptor (18); to date, only a few brain-penetrant PET tracers have been reported (19)(20)(21), and all of them are in the early phase of development. In the course of examining 11 C-GSK189254 in human subjects, Ashworth et al (17) observed that the ligand did not reach a washout phase in brain regions where it exhibits high binding, a reference tissue does not exist, and the radioligand is so potent that it is difficult to achieve tracer dose conditions-that is, that 11 C-GSK189254 does not satisfy most of the conditions mentioned here.…”
Section: See Page 1021mentioning
confidence: 99%